Analisis Kemampuan Pemecahan Masalah Matematis Siswa SMP Kelas VIII pada Materi Aljabar - Sri Handayani; Dadang Rahman Munandar (CV. Syntax Corporation Indonesia, 2023)
One of the problems that often occurs in learning mathematics is the ability to solve problems on certain subjects. This research has the objective of analyzing students' mathematical problem-solving abilities regarding algebraic material. In research, of course, using research methods, researchers decide to use qualitative descriptive methods. The study was carried out in an odd semester at SMP Negeri 1 Rawamerta in the 2022/2023 school year class VIII J. The population in this study was all class VIII J students of SMP Negeri 1 Rawamerta with a sample used of 15 students. The instrument in the research is a question in the form of a test on the ability to solve mathematical problems by means of data collection techniques. According to the results of the analysis that has been carried out, an average score was obtained from the mathematical problem solving ability of class VIII J students at SMP Negeri 1 Rawamerta on solving algebraic material problems, that is 32.25%. Students' mathematical concept ability in solving algebraic material problems in class VIII J students at SMP Negeri 1 Rawamerta can be categorized as low.